AN EXPLORATORY STUDY ON FOSTERING EARLY CAREER RESEARCHER GROWTH THROUGH AN INTERPROFESSIONAL UNDERGRADUATE MEDICAL CONFERENCE AT A PRIVATE SECTOR UNIVERSITY IN PUNJAB. : JPUMHS;2024:14:03,12 19.http://doi.org/10.46536/jpumhs/2024/14.03.529 - Kainat Javed1, Mahnoor Tariq2, Umair Bin Nasir3, Arooj Javed4 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
ABSTRACT BACKGROUND: This study explores at how undergraduate research conferences influence students' perspectives and promote career development. Through the use of the contextual learning concept, it explores how these conferences function as experiential learning opportunities and aid in the development of critical graduate competencies.METHODOLOGY: This investigation was qualitative design. 211 students who participated in Rashid Latif Medical College's Interprofessional Undergraduate Student Conference were interviewed to gather data, and theme analysis was used to pinpoint and match their skill improvement.RESULTS:The three main advantages of attending the conference, according to the students, were the opportunity to engage with other professionals, present papers and posters and get feedback, and fully experience the conference atmosphere. Many of the talents and qualities they reported were in line with the domains of the Five-Star and Seven-Star Doctor frameworks. In order to compare the projected results with the actual skill growth, the study also looked at student engagement. CONCLUSION: Conference planners can learn a lot from this study about how to create programs that optimize interprofessional undergraduate students' skill development. Additionally, it gives learning creators advice on how to help students get ready for these kinds of conferences. By emphasizing the importance of undergraduate research conferences for networking, improving communication skills, and cultivating competencies pertinent to undergraduate medical and allied health sciences students, the study closes a knowledge gap regarding how these events support skill development in interprofessional contexts.